Broad-spectrum humanized monoclonal neutralizing antibody against SARS-CoV-2 variants, including the Omicron variant - Wen, Kun; Cai, Jian-Piao; Fan, Xiaodi; Zhang, Xiaojuan; Luo, Cuiting; Tang, Kai-Ming; Shuai, Huiping; Chen, Lin-Lei; Zhang, Ricky Ruiqi; Situ, Jianwen; Tsoi, Hoi-Wah; Wang, Kun; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Therapeutic monoclonal antibodies (mAbs) against the SARS-CoV-2 spike protein have been shown to improve the outcome of severe COVID-19 patients in clinical trials. However, novel variants with spike protein mutations can render many currently available mAbs ineffective. Methods We produced mAbs by using hybridoma cells that generated from mice immunized with spike protein trimer and receptor binding domain (RBD). The panel of mAbs were screened for binding and neutralizing activity against different SARS-CoV-2 variants. The in vivo effectiveness of WKS13 was evaluated in a hamster model. Results Out of 960 clones, we identified 18 mAbs that could bind spike protein. Ten of the mAbs could attach to RBD, among which five had neutralizing activity against the ancestral strain and could block the binding between the spike protein and human ACE2. One of these mAbs, WKS13, had broad neutralizing activity against all Variants of Concern (VOCs), including the Omicron variant. Both murine or humanized versions of WKS13 could reduce the lung viral load in hamsters infected with the Delta variant. Conclusions Our data showed that broad-spectrum high potency mAbs can be produced from immunized mice, which can be used in humans after humanization of the Fc region. Our method represents a versatile and rapid strategy for generating therapeutic mAbs for upcoming novel variants.